Selection of mobile network operator using analytic hierarchy process (AHP) - Hassan, Nasruddin; Ahmad, Norfaieqah; Wan Mohd. Aminuddin, Wan Malissa (AENSI Publishing, 2013)
In Malaysia, Celcom, Maxis and DiGi are the most familiar mobile network operator subscribed by Malaysian. These three operators promote a variety of packages to attract mobile users. In this paper an Analytic Hierarchy Process model is built up to solve the multi-criteria decision making problem in selecting the most suitable mobile network operator. Four criteria associated with mobile network operator were considered and questionnaires regarding selection of mobile network operators were distributed. Celcom is found to be the most preferable mobile network operator while monthly commitment becomes the most important criteria in the selection process followed by monthly charges, rewards and value added services.